The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1055/s-0042-102061
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss unterschiedlicher Ablationsfrequenzen auf die klinischen Ergebnisse bei photorefraktiver Keratektomie unter Verwendung derselben Excimer-Laser-Plattform: Ein kontralateraler Vergleich

Abstract: The objective of this study was to evaluate postoperative clinical outcomes of photorefractive keratectomy (PRK) using different ablation frequencies. In this prospective, contralateral eye study, 56 eyes of 28 patients with myopia or myopic astigmatism were included. PRK was performed using the MEL90 excimer laser system (Carl Zeiss Meditec, Germany). One eye of each patient was treated with a repetition rate of 250 Hz, while the other one was treated with a repetition rate of 500 Hz. The treatment pattern in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this study, we performed PRK using the Mel 90 excimer laser with the Triple-A profile which is improved from previous ASA and TSA profiles in that it has better error compensation function and target asphericity control, which minimizes ablation depth, adjusts for spherical aberration and prevents myopic regression [ 39 ]. The surgeon can also choose a frequency up to 500 Hz across the surgery in Mel 90 excimer laser, which enables faster ablation time for correction [ 39 , 40 ]. Thus, clinical outcomes after PRK with the same optical zone size can differ according to which excimer laser used, and it therefore seems inappropriate to compare this study with clinical data from studies that used the previous version of the excimer laser for PRK in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we performed PRK using the Mel 90 excimer laser with the Triple-A profile which is improved from previous ASA and TSA profiles in that it has better error compensation function and target asphericity control, which minimizes ablation depth, adjusts for spherical aberration and prevents myopic regression [ 39 ]. The surgeon can also choose a frequency up to 500 Hz across the surgery in Mel 90 excimer laser, which enables faster ablation time for correction [ 39 , 40 ]. Thus, clinical outcomes after PRK with the same optical zone size can differ according to which excimer laser used, and it therefore seems inappropriate to compare this study with clinical data from studies that used the previous version of the excimer laser for PRK in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that the Triple-A profile with a frequency setting of 500 Hz was safe, efficient, and predictable for the correction of mild-to-moderate myopia [6]. Tandogan et al also found that ablation frequency was not a risk factor of haze after surgery [7]. However, the effect of Triple-A profile with a frequency setting of 500 Hz for the correction of high myopia remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Since introducing excimer lasers for refractive surgery, several million people have been successfully treated to decrease or eliminate their dependency on glasses or contact lenses to correct their ametropia [ 1 ]. Surface ablation procedures, such as photorefractive keratectomy (PRK) or laser epithelial keratomileusis (LASEK) and epi-LASIK, can be used very effectively to correct ametropia [ 2 ], and the risk for the development of keratectasia in uncompromised corneas is low [ 3 ]. However, patients’ visual acuity recovery is rather slow, and patients suffer from quite severe pain in the postoperative period.…”
Section: Introductionmentioning
confidence: 99%